PERSPEKTIF HUKUM EKONOMI SYARIAH TERHADAP PEMELIHARAAN DAN PEMBOCORAN RAHASIA DAGANG DI KALANGAN PENGUSAHA KECIL KULINER KOTA MATARAM: Indonesia - Dwina Meisonya; Heru Sunardi; Teti Indrawati Purnamasari (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
The strategy taken by business actors to improve products and services to consumers is to create a product innovation. This product innovation is generated from thoughts or ideas, ideas that are the most important part for everyone because they can have high economic value and are valuable. Interestingly, business actors in Mataram City actually have Intellectual Property Rights, which are not kept secret but are instead informed to other people. These business actors only realize that any information related to their business products is very valuable when there are competitors, so far they feel there is no problem because there are no competitors who have the same business.